SHAHABAT YANG DITERIMA RIWAYATNYA: KAJIAN TENTANG KUALITAS PRIBADI DAN KAPASITAS INTELEKTUAL (KE-DLABIT-AN DAN ‘ADALAT AL-SHAHABAH) - Ach Zayyadi (AT-TAJDID, 2017)
This paper used the method of librarian research and aims to reveal the companions of his history: the study of personal qualities and intellectual capacities (dlabit-an and 'Adalat al-Shahabah) In the hadith, it is explained about the urgency of friends in relation to the series transmission of hadith. Which, friends have an important role in the effort to transfer the religious information in the next period, so it can be said, without friends, the religious information will not reach the next period, even today. In this study concluded that there are two great views in the transmission of hadith. The first assumes that companions have a very qualified personal qualities that can not be doubted by anything. While the second, the classification and clarifying  level of personal quality of friends affected by many factors. The quality of the traditions narrated by the Companions is not merely a matter of personal quality ('just), but the personal capacity (dhabith) of a transmitter becomes something very urgent for the implementation of a true and responsible doctrine.